Developmental and Academic Learning differences for Pre-School Children in North Jeddah, Saudi Arabia - Al-Zoubi, Nidal Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2019)
The aim of the research was to determine the size of the problem of learning differentials for preschool children for the target group during the period from 20/4/1436 to 3/5/1436 AH, while applied to the sample studied during the period from 5/5/1436 to 13/5 / 1436 e. The researcher used the descriptive method of "survey study". The researcher applied some scientific tests and measurements to measure some learning differences on a sample of (100) children and their child (53 males and 47 females) in pre-school in Jeddah. The results of the study showed that the differences in visual memory were the most common learning differences (51%) and the auditory differences (25%), followed by learning differences (24%) and mathematical inference (24%) respectively. The results also showed significant differences between males and females in the tests of hyperactivity, dizziness, attention, social interaction, writing, and auditory perception for females, and males and females are equal in tests of social maturity, pre-reading, mathematical inference and visual memory. Among students born in 2010 and students born in 2011 in social maturity tests, social interactions, writing, auditory perception, visual memory, pre-reading for age 5, attention tests, impulse and hyperactivity. For (4) years, while there were no differences according to the variables (gender - age) in other measures. The researcher recommends taking into account the child's access to the level of maturity appropriate for learning to read and write and account, and not forced to do so in the pre-school, and interest in building programs of motor education for children and the need to apply to students outside the classroom. As well as the importance of focusing teachers on activities that are concerned with the development of the child's senses in general, and on audio-visual activities in particular, and assigning the task of pre-school teaching to qualified teachers in the field of child education.
Keywords: pre-school; learning differences; kinesthetic education programmes